Variation in Ruscogenin Contents in Ruscus aculeatus L. Growing Wild in Southern Turkey - TANSI, S.; KOKDIL, G.; KARAMAN, S.; TONCER, O. (Asian Journal of Chemistry, 2010)
The ruscogenin contents of the underground and aerial parts of Ruscus aculeatus (Liliaceae) collected from 6 different locations in southern Turkey were investigated by HPLC. The highest ruscogenin content (0.12 %) was recorded from the underground parts of R. aculeatus collected from Incebel/Osmaniye area of Turkey. Ruscogenin contents in aerial and underground parts of R. aculeatus varied the contents did not vary greatly in aerial parts.